2022
DOI: 10.3390/cancers14020394
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Exon 20 Insertion Mutations in Sinonasal Squamous Cell Carcinoma

Abstract: Recurrent epidermal growth factor receptor (EGFR)-activating mutations have been identified in a rare form of head and neck cancer known as sinonasal squamous cell carcinoma (SNSCC), a malignant disease with a 5-year mortality rate of ~40%. Interestingly, the majority of EGFR mutations identified in patients with primary SNSCC are exon 20 insertions (Ex20ins), which is in contrast to non-small-cell lung cancer (NSCLC), where the EGFR exon 19 deletion and L858R mutations predominate. These studies demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 107 publications
(184 reference statements)
0
7
0
Order By: Relevance
“…17,18 There is no evidence in clinical trials of SNCtargeted therapy, but there were some effective in vitro experiments of exon 20 mutation SNC by epidermal growth factor receptor gene (EGFR) exon 20 inhibitor targeted therapy, neratinib, which sparked a debate about the viability of SNC treatment. 19,20 On the other hand, the treatments in OC, OPC, and LC have gained potential to use targeted therapy and immunotherapy, such as nivolumab and cetuximab. Nivolumab and cetuximab are monoclonal antibodybased therapies that target Programmed death 1 (PD-1) and EGFR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 There is no evidence in clinical trials of SNCtargeted therapy, but there were some effective in vitro experiments of exon 20 mutation SNC by epidermal growth factor receptor gene (EGFR) exon 20 inhibitor targeted therapy, neratinib, which sparked a debate about the viability of SNC treatment. 19,20 On the other hand, the treatments in OC, OPC, and LC have gained potential to use targeted therapy and immunotherapy, such as nivolumab and cetuximab. Nivolumab and cetuximab are monoclonal antibodybased therapies that target Programmed death 1 (PD-1) and EGFR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that smoking and occupational hazards are strongly associated with human sinonasal SCC, 21,31,32 these tumours might also show a different behaviour than their canine counterparts. Currently, monoclonal antibodies especially against EGFR 69,70 and VEGFR 71 are being investigated in human sinus carcinoma 18–20 …”
Section: Discussionmentioning
confidence: 99%
“…68 Considering that smoking and occupational hazards are strongly associated with human sinonasal SCC, 21,31,32 these tumours might also show a different behaviour than their canine counterparts. Currently, monoclonal antibodies especially against EGFR 69,70 and VEGFR 71 are being investigated in human sinus carcinoma. [18][19][20] There are several limitations to this study: diagnosis was based on clinical findings as well as cytological or histological and diagnostic imaging reports.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations of differences between DN-SCC and IP-SCC include molecular differences that may impact clinical behavior and outcomes. For instance, a recent study reported a higher prevalence of EGFR mutations in IP-SCC that are less frequently observed in DN-SCC (44) . Additionally, a recent study demonstrated progressive upregulation of several genes unique to malignant transformation of IP-SCC that may impact different outcomes compared to DN-SCC (45,46) .…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 99%